Technologies for African Agricultural Transformation (TAAT II). Fish Compact: Upscaling Aquaculture Technologies to Boost Value Chain - Fregene, Bernadette; Akuwa, Elizabeth; Iyangbe, Charles (WorldFish, 2025)
The TAAT II Fish Compact Fact Sheet provides a concise overview of the project’s objectives, technologies, and impacts for partners and stakeholders:” The initiative promotes fast-growing, climate-resilient fish species, low-cost quality feed, and climate-smart processing technologies. It builds capacity among farmers, youth, women, and value chain actors while strengthening aquabusiness development and innovation platforms. Expected outcomes include 80% farmer access to improved fish seed, a 20% rise in production, and a 20–30% reduction in fish imports, contributing to improved nutrition, job creation, and sustainable aquaculture growth across Africa. The TAAT II Fish Compact, led by WorldFish and supported by the African Development Bank, aims to enhance aquaculture productivity and value chain development in 11 African countries.